EDUKASI KEBIJAKAN BUPATI GROBOGAN NOMOR 57 TAHUN 2022 TENTANG PERCEPATAN STUNTING DAN INTERVENSI GIZI PADA STUNTING - Sutiyono; Wahyu Riniasih; Muhammad Makmun; Sri Temu; Nurya Kumalasari (LPPM AN Nuur, 2025)
Background: Stunting is a serious public health problem worldwide, particularly in developing countries. The prevalence of stunting is 21.6%, meaning that 1 in 5 children under five in Indonesia experience chronic growth problems. Objective: The purpose of this community service is to educate the Regent about the Regent's policy on providing family nutrition interventions. Method: The method used in this community service is a health education method regarding the Regent's policy on providing family nutrition interventions to the community in Krangganharjo Village, Toroh District. Results: Based on the post-test results, 100% of the community was able to identify good policies and interventions for providing family nutrition. The expected impact is the community's willingness to implement nutritious food in accordance with the Grobogan Regent's Regulation Number 57 of 2022 regarding family nutrition interventions